A chronology of cancer. (13th April 2011) - Camidge, D Ross
Abstract : This comprehensive book describes a disease that kills seven million people globally a year. The stories of key doctors and patients, says D Ross Camidge, enrich this tale of cancer, from its first documentation to hypotheses about future treatment